2011
DOI: 10.4103/0019-5049.76597
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic management in patients with glucose-6-phosphate dehydrogenase deficiency undergoing neurosurgical procedures

Abstract: Glucose-6-phosphate dehydrogenase (G-6-PD) deficiency is an X-linked recessive enzymopathy responsible for acute haemolysis following exposure to oxidative stress. Drugs which induce haemolysis in these patients are often used in anaesthesia and perioperative pain management. Neurosurgery and few drugs routinely used during these procedures are known to cause stress situations. Associated infection and certain foodstuffs are also responsible for oxidative stress. Here, we present two patients with G-6-PD defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…That leads to increased vascular permeability and production of oxidative radicals by neutrophils and inflammatory cells. 5 During active infections, oxygen free radicals are produced either by inflammatory neutrophils or by use of antimicrobials and may precipitate haemolysis during the perioperative period. Therefore adequate treatment of active infections and administrating an appropriate antibiotic (ceftazidime) which does not precipitate perioperative haemolysis is of extreme importance.…”
Section: Discussionmentioning
confidence: 99%
“…That leads to increased vascular permeability and production of oxidative radicals by neutrophils and inflammatory cells. 5 During active infections, oxygen free radicals are produced either by inflammatory neutrophils or by use of antimicrobials and may precipitate haemolysis during the perioperative period. Therefore adequate treatment of active infections and administrating an appropriate antibiotic (ceftazidime) which does not precipitate perioperative haemolysis is of extreme importance.…”
Section: Discussionmentioning
confidence: 99%
“…Beutler [ 3 ] reported that halothane has no effect on G6PD activity, but isoflurane and sevoflurane have, although there are few case reports where isoflurane and sevoflurane were safely used in G6PD deficiency patients. [ 4 ] Propofol is considered as safe in G6PD deficiency patient and we also used it for induction and maintenance of anesthesia in our case. The safety of use of propofol in neonates and infants is debatable,[ 5 ] but recent reports suggest that it can be safely used in infants.…”
mentioning
confidence: 99%
“…Various drugs used for anesthesia and analgesia, antibiotics, surgical stress, infection, conditions associated with generation of free radicals like perioperative ischemia, reperfusion, hypothermia and acidosis are known to cause oxidative stress and thereby hemolysis in G6PD deficient patient. [ 1 ] Peripheral limb ischemia and reperfusion is commonly encountered situation in orthopaedic surgery with tourniquet use. Young age, male gender, negative family history of G6PD deficiency, presence of fever and vomiting and high alkaline phosphatase are the predictors for severe hemolysis[ 2 ] as in this case.…”
mentioning
confidence: 99%
“…Laboratory findings following a hemolytic episode are anaemia, decreased serum haptoglobulin and an elevated indirect bilirubin. Benzodiazepine, propofol, ketamine, fentanyl, codeine, paracetamol, inhalational agent namely isoflurane and sevoflurane are safe for perioperative use,[ 1 3 ] α 2 receptor agonist, dexmeditomedine have also been used successfully for maintenance of anesthesia. [ 4 ] Very few case reports mentions the use of local anesthetic, bupivacaine[ 5 ] for regional anesthesia but lignocaine has been reported to cause hemolysis in G6PD deficiency.…”
mentioning
confidence: 99%